Why Angiotensin II is a Poor Choice for Circulatory Support of Ventilated COVID-19 Patients Compared to Vasopressin - Speth, Robert C.; Bader, Michael (Medical Research Archives, 2022)
Early in the COVID-19 pandemic when it was first reported that SARS-CoV-2 used membrane-bound angiotensin-converting enzyme-2 (ACE2) as its receptor for entry into cells, warnings were raised against the use of angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs) because of their potential to increase ACE2 expression. These reports ignored the adverse effects that the renin-angiotensin system (RAS) exerts on the cardiovascular system and kidneys via its primary hormone angiotensin (Ang) II acting upon AT 1 receptors that could exacerbate the cytokine storm induced by SARS-CoV-2 1 .  At one point it was even recommended that COVID-19 patients suffering from cardiovascular collapse be administered Ang II to restore blood pressure rather than norepinephrine or vasopressin 2 . An alternative strategy for treating COVID-19 was the administration of soluble ACE2 (sACE2) to act as a decoy receptor for the virus, misdirecting it away from vulnerable cells expressing membrane bound ACE2 3-5 . However, a paper published in early 2021 6 described a scenario in which sACE2 and vasopressin played essential roles in SARS-CoV-2 infection of cells vulnerable to the virus. This commentary challenges both the 2 and 6 reports based upon their misconceptions and technical errors that pose a threat to the administration of life-saving therapies for severely affected COVID-19 patients.